Effects of post-mortem aging process on characteristic water-soluble taste-active precursors in yellow-feathered broilers - Na Xu; Xianming Zeng; Lingyun Li; Xinyue Zhang; Peng Wang; Minyi Han; Xinglian Xu (Food Science and Human Wellness)
Chilled chicken has become the mainstream of chicken consumption. In order to explore the effect of post-mortem aging on water-soluble flavor precursors of chicken, pH, adenosine triphosphate (ATP) degradation, flavor nucleosides, free amino acids and water-soluble low molecular weight peptides were determined using Qingyuan partridge yellow-feathered broilers as material during 0–4 °C post-mortem aging in 48 h. The results showed that the pH value fell to the limit pH 5.64 (4 h) in chicken breast and 6.21 (3 h) in thigh. Regardless of chicken breast or thigh, ATP dropped rapidly within 3 h. It was found that the K-value in chicken thigh was the lowest at 2 h indicating the freshness was the best. Considering the equivalent umami concentration (EUC), the value at 3 h and 4 h was relatively high, but the corresponding electronic tongue umami value was not high, which further showed that the water-soluble low molecular taste peptide played an important role on the post-mortem aging process. Combined with cluster analysis and partial least squares discriminant analysis (PLS-DA), it was preliminarily inferred that the optimal time for chilled chicken during 0–4 °C post-mortem aging was 2 h, which could provide a theoretical basis for the further processing of fresh chicken.